Low self-control and high group identification - The aftermath of Umbrella Movement - Lee, Annissa (Advances in Social Sciences Research Journal, 2018)
The seed of “localism” was sown in Hongkonger’s mind since the Leftist Riot in 1967. In recent years, the demolition of Queens Pier, the refusal to implement universal suffrage for the selection of the Chief Executive, the crackdown on illegal street food hawkers and the parallel trading among mainland tourists kept encouraging the revival of “localism” and frequent collective actions. Mongkok Riot is the second largest protest ever happened since Umbrella Movement and is a collective action to denounce the seriousness of socio-political problems. This study aimed to explore the underlying psychological elements of collective action participation—emotional and rational decision-making processes. Pro-movement respondents (n = 1413) aged between 19 and 67 were included and self-reported questionnaire was used as the main measure. Results revealed that there were distinct differences across self-control and group identification between rioters and protestors. In which, protestors showed high self-control and low group identification than rioters. Low level of self-control and high level of group identification were found to be an individual characteristic for repeated collective action participations. The findings also revealed that self-control, centrality to group and in-group affect are significant variables in predicting collective action participation. This study implied that the likelihood of collective action participation is determined by decision-making process which strongly influenced by self-control and group identification.